Porous silicon based intravitreal platform for dual-drug loading and controlled release towards synergistic therapy - David Warther; Ying Xiao; Fangting Li; Yuqin Wang; Kristyn Huffman; William R. Freeman; Michael Sailor; Lingyun Cheng (Taylor & Francis Group, 2018)
The number of blind and low vision persons in the US is projected to increase to 5.68 million by 2020. The eye diseases causing loss of vision are life-long, chronic, and often need protracted presence of therapeutics at the disease site to keep the disease in remission. In addition, multiple pathologies participate in the disease process and a single therapy seems insufficient to bring the disease under control and prevent vision loss. This study demonstrates the use of porous silicon (pSi) particles sequentially loaded with daunorubicin (DNR) and dexamethasone (DEX) to create a synergistic intravitreally injectable dual-drug delivery system. DEX targets chronic inflammation while DNR inhibits excessive cell proliferation as well as suppresses hypoxia-inducible factor 1 to reduce scarring. This pSi-based delivery system releases therapeutic concentrations of DNR for 100 days and DEX for over 165 days after a single dose. This intravitreal dual-drug delivery system is also well tolerated after injection into the rabbit eye model, attested by ocular biomicroscopy, ocular tonometry, electroretinography, and histology. This novel dual-drug delivery system opens an attractive modality for combination therapy to manage refractory chorioretinal diseases and further preclinical studies are warranted to evaluate its efficacy.